Letter (copy) : Foodstuffs for Spain - Tewson, Vincent
029-0052-001 HVT/FC/138. Secretary's. 7th January, 1938. Mr. E. Winstanley, The Co-operative Wholesale Society Ltd., 1, Balloon Street, MANCHESTER, 4. Dear Mr. Winstanley, FOODSTUFFS FOR SPAIN. I thank you for your letter of the 6th instant from which I note that the s.s. MADGE LLEWELLYN has been substituted by the s.s. DELLWYN. It is also noted that arrangements are being made for the transhipment at Oran of the goods shipped by the s.s. HARTBRIDGE. Yours sincerely, Assistant Secretary. 292/946/29/52